Spiritualitas Islam Sebagai Jalan Pemulihan Bagi Pecandu Narkoba: Tinjauan QS Al-Ma’arij Ayat 19-23 - Bachmid, Nurul Inayah; Mustaqimah; Syahril Dja’fara; Yanto Hiliwilo (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2025)
NAPZA is an acronym for narcotics, psychotropics, and other addictive substances. In the perspective of the Qur’an, drugs are equated with khamar because both of them lose consciousness. Most scholars agree on the prohibition of drugs or something similar to it. Drug abuse is a major problem that threatens many individuals and society as a whole. Conventional recovery is often less effective in providing long-term solutions for drug addicts. From an Islamic perspective, spiritual recovery can be an alternative. This article aims to examine the application of Islamic spiritual recovery methods in dealing with drug addicts by referring to surah al-Ma’arij verses 19-23. The verse describes the state of human beings who like to complain, entangled in various temptations and difficulties in life, which can be related to the condition of drug addicts. This research was conducted using the method of interpretation analysis of surah al-Ma’arij verses 19-23, a qualitative approach to explore the application of Islamic values in the recovery of drug addicts. By taking advantage of this approach, it is proposed that Quran-based Islamic spiritual restoration could provide better solutions to those who are entangled in drug addiction.